At the mercy of the winds and imagination: A letter to Mario Osorio Marques (Revista Contexto & Educação, 2025)
Aiming to discuss the specificity of school education and to uphold the importance of dialogue in the teaching and learning relationship, we examine issues that affect us as teachers in the exercise of thought, especially those involving the increasing emphasis on technology in the educational process. By writing to Mario Osorio Marques, we revisit his teachings, which allow us to shed new light on everyday matters, to problematize them by questioning his body of work, and to support our educational arguments centered on the humanity of the individual. In preparing this text, we adopted a critical hermeneutic dialogue, seeking in the philosopher of education’s thinking—alongside other theorists—support for broadening our understanding of contemporary times. By choosing to write a letter to the researcher, we establish a mode of dialogue across time with the thought of this important intellectual in the field of education, thereby keeping him close to our readings of the world. As a result, we unsettle contemporary chronotopies, whose events have cornered schools and their work; we demonstrate the questioning of a supposed "life" of technology that has been strongly propagated; and we recognize the need to speak about fear to find encouragement. We conclude that placing our bets on dialogue, both as an approach and as a school-level educational goal, offers a pathway toward affirming a human-centered, transformative, and emancipatory form of education.
Keywords: Problematizing dialogue; otherness; transformative education; technologies; school teaching